The International Criminal Court Jurisdiction Towards The Deportation Issues In Myanmar - Bugivia Maharani Setiadji Putri; Sefriani Sefriani (Yustisia Jurnal Hukum, 2021)
This research aims to comprehensively analyze the International Criminal Court’s jurisdiction in adjudicating gross violations of human rights involving a non-party state of the 1998 Rome Statute and its application to the perpetrators of deportation against the Rohingya with Myanmar as the non-party state. The results showed that this jurisdiction can be implemented under three conditions, first, the crime is committed by nationals of a non-party state on the territory of a state party to the Statute. Second, the UN Security Council refers a situation to the International Criminal Court in its resolution. Third, through an ad hoc declaration that a non-party state of the Rome Statute accepts the International Criminal Court’s jurisdiction. Since the territorial jurisdiction of the International Criminal Court covers crimes that occur wholly or partly on the territory of a state party, it can be applied to the deportation against the Rohingya in Myanmar. This involved the fleeing of this ethnic group from attacks by the Government of Myanmar to Bangladesh, a state party to the 1998 Rome Statute